Claisen rearrangement of allyl phenyl ether over zeolites beta, mordenite and Y - Wagholikar, S. G.; Mayadevi, S.; Jacob, Nalini E.; Sivasanker, S. (Microporous and Mesoporous Materials, 2006)
The Claisen rearrangement of allyl phenyl ether (APE) to o-allylphenol was investigated over zeolites beta (BEA), mordenite (MOR) and Y (FAU) with different Si/Al ratios. Over the zeolite catalysts, the allylphenol cyclized to produce 2,3-dihydro-2-methyl benzofuran. Larger catalyst loading, higher reaction temperatures and longer run duration favored the formation of the ring compound. Conversion was small over MOR and FAU although they possessed higher acidity (as measured by the temperature programmed desorption of ammonia) compared to BEA. Studies using BEA revealed that the nature of the solvent influenced the reaction rate. The order of reactivity in the solvents was, benzene > EDC (1,2-dichloroethane) > toluene > TCE (1, 1,2,2-tetrachloroethane) >> ACN (acetonitrile). The intermediate allylphenol reacted with the aromatic solvents to produce byproducts when benzene and toluene were used as solvents. A kinetic analysis assuming first order series and parallel reactions is presented. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: allyl phenyl ether; allylphenol; Benzofuran; Claisen rearrangement; zeolites

Cellulose supported layered double hydroxides for the adsorption of fluoride from aqueous solution - Mandal, Sujata; Mayadevi, S. (Chemosphere, 2008)
Cellulose supported layered double hydroxides (CSLDHs) were synthesized and tested for adsorption of fluoride in aqueous medium. Three samples of cellulose supported LDHs were synthesized by varying the LDH loading on cellulose. The raw cellulose, unsupported LDH and cellulose supported LDHs were characterized by XRD, SEM and BET surface area. Batch adsorption as well as fixed-bed column experiments were performed for determining the fluoride adsorption characteristics of CSLDHs. The fluoride adsorption properties of CSLDHs were found to be superior to that of reported adsorbents, including activated alumina and carbon nanotubes. Defluoridation capacity of the CSLDHs was 2-4 times higher than that of unsupported LDH. The cellulose supported LDH, CSLDH-50, having an LDH loading of 27% showed maximum fluoride uptake capacity (5.29 mg g(-1) of CSLDH, 25.18 mg g(-1) of LDH) in fixed-bed column study. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Adsorption; cellulose; Fluoride; Layered double hydroxide